STATISTICAL ANALYSIS INTENSIVE INVESTMENT FROM THE UKRAINIAN REGIONS - Корепанов, Г. С. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2014)
The article deals with evaluation of the intensity of direct investment from the regions of Ukraine according to the gross regional product. The paper proposes to conduct evaluation degree of concentration of FDI from Ukraine’s regions using the Herfindahl-Hirschman index.